Long-Term Effect of Decompressive Craniectomy on Intracranial Pressure and Possible Implications for Intracranial Fluid Movements. Issue 7 (16th November 2020) - Lilja-Cyron, Alexander; Andresen, Morten; Kelsen, Jesper; Andreasen, Trine Hjorslev; Fugleholm, Kåre; Juhler, Marianne
Graphical Abstract: